Rational design and engineering of a microbial cell factory for 3-hydroxypropionic acid production - Chaves, Gabriel Luz (Universidade Federal de São Carlos, 2021)
The US Department of Energy ranked the 3-hydroxypropionic acid (3-HP) among the Top 10 most promising value-added chemicals that can be derived from biomass in a biorefinery. This acid has great potential to serve as a building block for the industry, serving as raw material for paints, coatings, and polymers. Nevertheless, its production from chemical routes encompasses processes that are highly toxic and environmentally harmful. In this context, fermentative bioprocesses are a promising alternative for 3-HP production. Here, we proposed the obtention of an Escherichia coli strain genetically modified to produce 3-HP through the β-alanine pathway, yet poorly studied. To build an E. coli strain able to produce 3-HP, the genes that encode the last three reactions of the pathway were cloned and combined in the same plasmid (pEbtyGpD): pa0132 from Pseudomonas aeruginosa, ydfG from E. coli, and panD from Corynebacterium glutamicum. This first engineered strain, named PS100, produced up to 0.338 ± 0.044 g/L of 3-HP after 24 h of induction with IPTG using glucose as a carbon source. Surprisingly, cultivations on a mixture of glucose and xylose (1:1 on C-mol basis) yielded a final titer of 1.040 ± 0.050 g/L by this strain, from the same substrate amount. To optimize the production obtained from PS100, new genetic modifications were investigated through in silico optimization of a genome-scale metabolic model of E. coli K-12 MG1655. The model iML1515 was modified to include the heterologous reaction of β-alanine conversion to malonic semialdehyde, and three reactions were identified as potential metabolic targets for enhancing 3-HP production by E. coli cells: the reactions of alanine racemase (ALAR), L-alanine aminotransferase (ALAT), and L-valine transaminase (VALTA). These target reactions were modified in the strain PS100, generating the strain PSO107 that was able to improve nearly 2-fold the final titer of the acid when compared to PS100 in cultivations with glucose as carbon source, reaching 0.743 ± 0.016 g/L of 3-HP. For cultivations with the glucose:xylose mixture, a 10% increment was observed for the PSO107 strain compared to PS100, with the former reaching 1.147 ± 0.015 g/L of 3-HP. These results confirm that the targets predicted by the evolutionary optimizations of the genome-scale metabolic model were assertive and enabled an increment in the final production of 3-HP by the engineered E. coli strain.
Desenho e construção racional de uma fábrica celular para produção de ácido 3-hidroxipropiônico
Keywords: Modelo metabólico em escala Genômica; Ácido 3-hidroxipropiônico; Beta-alanina; Biorrefinarias; Fábricas celulares; Engenharia metabólica; Metabolic engineering; Genome-scale metabolic model; 3-hydroxypropionic acid; Biorefinery; Beta-alanine; Microbial cell factory; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA